Efektivitas Pelayanan Berbasis Online Sistem Antrian Terpadu (SISTER) di Plasa Telkom Garut - Pasciana, Rostiena; Iriany, Ieke Sartika; Muhtadi , Arip Hilman (Jurnal Pemerintahan dan Politik, 2024)
The focus of this research is on the effectiveness of the online service based on the Integrated Queuing System (SISTER) at Plasa Telkom Garut. This SISTER is an innovation and modernization of Telecommunication company services for fulfill customer needs in the PSBB situation. Simply by using a smartphone, customers can access the SISTER application anywhere and anytime according to the service schedule. The purpose of this research is to determine the effectiveness of SISTER Plasa Telkom Garut online services. The research method used is descriptive qualitative approach. Data collection was carried out by observation, documentation, and interviews with 8 informants who considered representative consisting of Plasa Telkom Garut as service providers and customers. The assessment of the effectiveness of sister services is seen from 3 aspects, namely the achievement of program objectives, integration and adaptation of services. The results of the study show that the SISTER is still not effective in giving customer service needs, there are still customers who have not been able to access technology, the socialization of services are still fixated on the distribution of brochures or flayers. In addition, from the results of the study, it is known that the supporting and inhibiting factors of the implementation of SISTER services at Plasa Telkom Garut.